Solvent Impact on Langmuir and Langmuir–Schaefer Films of Soluble Main-Chain Poly(fullerene)s Based on C60 - de Lima Citolino, Lucas Vinicius [UNESP]; Santos Silva, Hugo; Silva Agostini, Deuber Lincon [UNESP]; Hiorns, Roger Clive; Bégué, Didier; de Almeida Olivati, Clarissa [UNESP] (Wiley, 2024)
Understanding the morphology and electronic properties of poly(fullerene)s is crucial for the development of new organic devices. This work addresses the fabrication and characterization of Langmuir–Schaefer (LS) films of poly(fullerene)s based on C60 with short (HSS8) and long (HSS16) sidechains, solubilized in chloroform or xylene. In addition, density functional theory (DFT) calculations are used to optimize the molecular geometries, determine energies, and investigate the influence of solvent applied. Depending on the organic solvent, floating material isotherms indicate the formation of disordered aggregates in the aqueous subphase. The influence of solvent in LS films is also evidenced by way of atomic force microscopy (AFM), UV-vis, and cyclic voltammetry (CV) measurements. From DFT calculations, the arms of the poly(fullerene)s start to extend from an initial position of surrounding the fullerene sphere. In AFM measurements, depending on the organic solvent, the roughness significantly reduces, while the homogeneity is much higher. In UV-vis and CV measurements, the propensity to form aggregates depends mainly on the polarization of the solvent and is directly related to the maximum absorption, oxidation, and reduction peaks. From the optical bandgap energy values, the poly(fullerene)s studied here present high potential for application in organic electronic devices.
Keywords: Langmuir–Schaefer; poly(fullerene)s; structure–optoelectronic property relationships; thin films